3D Adaptive Optical Nanoscopy for Thick Specimen Imaging at sub-50 nm Resolution - Xiang Hao; Allgeyer, Edward S; Antonello, Jacopo; Watters, Katherine; Gerdes, Julianne A; Schroeder, Lena K; Bottanelli, Francesca; Zhao, Jiaxi; Kidd, Phylicia; Lessard, Mark D; Rothman, James E; Cooley, Lynn; et al. (bioRxiv, 2020)
Understanding cellular organization demands the best possible spatial resolution in all three dimensions (3D). In fluorescence microscopy, this is achieved by 4Pi nanoscopy methods that combine the concepts of using two opposing objectives for optimal diffraction-limited 3D resolution with switching fluorescent molecules between bright and dark states to break the diffraction limit. However, optical aberrations have limited these nanoscopes to thin samples and prevented their application in thick specimens. Here, we have developed a nanoscope that, by utilizing an advanced adaptive optics strategy, achieves sub-50 nm isotropic resolution of structures such as neuronal synapses and ring canals previously inaccessible in tissue. Competing Interest Statement J. B. discloses a significant financial interest in Bruker Corp. and Hamamatsu Photonics.